Flipped Learning Approaches and Student’s Academic Performance in Economics in Selected Government Secondary Schools within the Bamenda Municipality, North West Region, Cameroon - Ambengwa, Bi Stefanie; Ambei Moses Chu (American Journal of Arts, Social and Humanity Studies, 2024)
Purpose: The purpose of this research was to examine the impact of flipped learning approaches on the academic performance of students in economics in selected government secondary schools within Bamenda I and II municipalities. The study aimed to assess the effects of discussion-oriented flipped learning and the flipped teacher approach. The study involved 88 students from three government secondary schools out of a total of 460 students. Materials and Methods: The research used a quasi-experimental design and a mixed method sampling technique, with three schools (G.B.H.S Bamenda and Bamendakwe) as the experimental groups and one (G.H.S Bangshie) as the control group. Data was collected over a 3-week research period using pretest and posttest research instruments. Findings: The results, analyzed using mean scores and ANCOVA, showed a positive impact of flipped learning approaches on the academic performance of economics students compared to traditional methods. The mean scores of all flipped approaches were higher in the experimental groups at significant levels lower than 0.05, leading to the rejection of the null hypothesis. Implication to Theory, Practice and Policy: The study recommended the integration of discussion-oriented, group-based, and flipped teacher approaches into teaching practices to enhance students' academic performance in economics. It also suggested that the government provide training and support for teachers to develop their skills in using these innovative teaching approaches and recommended that educational institutions prioritize technology integration in classrooms to facilitate effective use of flipped learning approaches. The findings have implications for educational policymakers, teachers, and educational institutions seeking to improve student outcomes in economics and other subjects.